Government Authority Transfer of Legal Entity of Indonesian Football Association Indonesian Football Welfare - Raditya Feda Rifandhana; Indro Budiono; Zenia Dwitya Pratidina; Rizky Herdian Herdiansyah; Selvia Wisuda; Suardi Suardi; Muhajir Muhajir; Muhammad Dahlan; Ayu Dian ingtias (JED (Jurnal Etika Demokrasi), 2023)
Indonesia is a country that has excellent sports achievements in the international world, one of which is football, the sports field is under the care of the Ministry of Youth Sports, coordinated with the Indonesian National Sports Committee and the Indonesian Football Association, but a few years ago, football achievements were constrained by an event that took many victims and lack of player welfare, so that there is a need for government authority in improving the welfare of football player athletes by transferring the status of PSSI legal entities? This study aims to transfer the legal entity of PSSI and improve the welfare of football player athletes, in this study using Normative Juridical research, with an approach to legal theories, aims to help complement this research. The resulting study found that football players athletes were less guaranteed welfare and the findings from research at PSSI contained corruption, so it was necessary to transfer the status of PSSI legal entities. Furthermore, there is a need for government authority and the transfer of PSSI legal entities and improve the welfare of football player athletes based on laws and regulations.